Hubungan Frekuensi dan Komposisi Zat Gizi Sarapan serta Aktivitas Fisik Terhadap Konsentrasi Belajar pada Remaja di SMA Sejahtera 1 Depok - Tengku Alvira Yusmaini (2020)
Adolescents needs a good concentration because it is needed in the learning process. Concentration of learning is to focus on what is learned. There are several factors that can affect the concentration of learning. This study was aimed to find out the relationship between frequency and composition of nutrients in breakfast and physical activity with concentration of learning in adolescents at Sejahtera 1 Senior High School Depok. This study was a quantitative research by using a cross sectional design. Simple random sampling was used and 71 respondens were randomly selected. Data were obtained through self-administered questionnaires and interview. The univariate analysis showed that the concentration of learning most of respondens (52,1%) was classified as good. Bivariate analysis was performed by using chi-square test showed relationship between frequency of breakfast (¬p-value¬=0,384), energy adequacy level of breakfast (¬p-value¬=0,133), protein adequacy level of breakfast (¬p-value¬=0,451), fat adequacy level of breakfast (¬p-value¬=0,304), carbohydrate adequacy level of breakfast (¬p-value-=0,050), and physical activity (¬p-value¬=0,581) with concentration of learning. The conclusion obtained in this study were no relationship between frequency of breakfast, energy adequacy level of breakfast, protein adequacy level of breakfast, fat adequacy level of breakfast, and physical activity with concentration of learning, but there was relationship between carbohydrate adequacy level of breakfast with concentration of learning in adolescents at Sejahtera 1 Senior High School Depok. Keywords : Adolescents, Frequency of Breakfast, Composition of Nutrients in Breakfast, Physical Activity, Concentration of Learning